2009
DOI: 10.1111/j.1349-7006.2008.01052.x
|View full text |Cite
|
Sign up to set email alerts
|

Inverse correlation of the up‐regulation of FZD10 expression and the activation of β‐catenin in synchronous colorectal tumors

Abstract: T he Wnt signal pathway is an essential signal pathway for multicellular organisms with diverse biological consequences. A large number of components are involved in signal transduction, one of which is the Frizzled homolog protein (FZD) that serves as a seven-pass transmembrane receptor for Wnt ligands. So far 10 members of FZD family genes have been identified based on structural and functional homologies. Colorectal cancers (CRCs) are prototype tumors and the Wnt signal pathway is profoundly involved in CRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 17 publications
3
30
0
Order By: Relevance
“…1H) (Jho et al, 2002;Huang and Schier, 2009). Conversely, a role of fzd10 in the Wnt/PCP pathway, as suggested by studies in synovial sarcomas and synchronous colorectal tumors Nagayama et al, 2009), was excluded because defects in convergent extension movement, such as widened somite and abnormal ntl, hgg1 (ctsl1b -Zebrafish Information Network) and/or dlx3 staining, were not detected in fzd10 morphants (supplementary material Fig. S2O-R).…”
Section: Resultsmentioning
confidence: 99%
“…1H) (Jho et al, 2002;Huang and Schier, 2009). Conversely, a role of fzd10 in the Wnt/PCP pathway, as suggested by studies in synovial sarcomas and synchronous colorectal tumors Nagayama et al, 2009), was excluded because defects in convergent extension movement, such as widened somite and abnormal ntl, hgg1 (ctsl1b -Zebrafish Information Network) and/or dlx3 staining, were not detected in fzd10 morphants (supplementary material Fig. S2O-R).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, BRMS1L 29 , EMT 30 and enhanced cancer invasiveness and metastasis [30][31][32] . Furthermore, qRT-PCR verified that WNT9B and WNT10B, two important Wnt ligands, were reduced by BRMS1L for 1.43-and 1.61-fold, respectively, whereas FZD10 (frrizled class receptor 10), a Wnt signalling receptor [33][34][35] , was reduced by 84% (Po0.001, t-test, Fig. 3b).…”
Section: Reduced Brms1l Is Associated With Breast Cancer Metastasismentioning
confidence: 86%
“…Wnt signalling pathway has been shown to control self-renewal and differentiation of cancer cells 29 , and aberrant activation of Wnt signalling leads to EMT in breast epithelial cells 41,42 . As a receptor for the Wnt pathway, FZD10 is expressed at high level in colorectal cancers, gastric cancers, as well as in synovial sarcomas, and is associated with the activation of Wnt signalling in these cancers 33,34,43 . For instance, FZD10 activates the non-canonical Wnt/JNK pathway in synovial sarcoma cell 34 and enhances their anchorage-independent growth.…”
Section: Discussionmentioning
confidence: 99%
“…Since the rapid internalization would be one of the important factors of 90 Y-MAb 92-13 efficacy as described previously [26], FZD10 would be a suitable target of RIT. It was reported that FZD10 was expressed highly in approximately onequarter of colon cancer [27], up-regulated in 7 cases of 37 informative cases of lung cancer [28] and in a subset of gastric cancer. Therefore, 90 Y-MAb 92-13 would be a potential therapeutic agent for application to a variety of cancers.…”
Section: Discussionmentioning
confidence: 99%